Kenyan Muslims women in media and politics: Fighting for Legitimacy (Global Journal of Human-Social Science, 2012)
Introduction -Kenyan Muslim women perceive of themselves as a marginalized lot in terms of participation in the public sphere. Each day to them is a struggle to be included in the decision making levels of the government. They are fighting for visibility and recognition especially in the political and governing processes. Kenyan Muslims women are adamant in negotiating for their political space. This struggle is even more intricate due to religion and their being a minority group. Consensus building has not fully succeeded in empowering women to be full partners in all decision making processes. In most Muslim Non-Governmental organizations, women are minimally involved in the organizational structures and are only useful in family matters. The public sphere is reserved for men.
Keywords: Marginalized; empowering; negotiating